2013
DOI: 10.1371/journal.pone.0071036
|View full text |Cite
|
Sign up to set email alerts
|

T4 Phage and Its Head Surface Proteins Do Not Stimulate Inflammatory Mediator Production

Abstract: Viruses are potent activators of the signal pathways leading to increased cytokine or ROS production. The effects exerted on the immune system are usually mediated by viral proteins. Complementary to the progress in phage therapy practice, advancement of knowledge about the influence of bacteriophages on mammalian immunity is necessary. Particularly, the potential ability of phage proteins to act like other viral stimulators of the immune system may have strong practical implications for the safety and efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 27 publications
8
67
1
3
Order By: Relevance
“…Taken together, these data indicate that phage treatment did not elicit an appreciable acute immune response. Similar results were reported by Miernikiewicz et al 18 Our study also investigated the impact of phage treatment on pig gut microbiome. In general, the gut microbiome of pigs in our study, regardless of treatments, resembled the typical swine microbiome shown previously.…”
Section: Discussionsupporting
confidence: 86%
“…Taken together, these data indicate that phage treatment did not elicit an appreciable acute immune response. Similar results were reported by Miernikiewicz et al 18 Our study also investigated the impact of phage treatment on pig gut microbiome. In general, the gut microbiome of pigs in our study, regardless of treatments, resembled the typical swine microbiome shown previously.…”
Section: Discussionsupporting
confidence: 86%
“…Second, contrary to viruses used in viral gene therapy, bacteriophages are unable to penetrate eukaryotic cells. Third, from an immunological point of view, bacteriophages do not elicit a significant acute inflammatory response in mammals as shown by several studies on both purified structural proteins and entire virions (17,54). In our work, we observed a non-significant increase in BAL fluid total proteins in bacteriophage-treated mice compared to control mice 6 hours post-infection (208 and 140 µg/mL, respectively).…”
Section: Discussionsupporting
confidence: 60%
“…Miernikiewicz et al () examined the impact of purified bacteriophage T4 and the highly purified surface proteins of its head (i.e. gp23 and gp24) on the profiles of inflammatory mediators and other inflammation‐related factors (i.e.…”
Section: Nonclinical Studiesmentioning
confidence: 99%